MODEL PEMBELAJARAN MELALUI MEDIA SCHLANGENLEITERSPIEL UNTUK PENINGKATAN KEMAMPUAN BERBICARA GURU BAHASA JERMAN - Kharis, M. (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2010)
The activity of public service or social devotion is aimed at improving the speaking skills among German teachers in high schools in Malang through schlangenleiterspiel. This way is to facilitate their teaching through Rollenspiel to make their class more interesting and fun. The method used to solve the problems in this activity covers speech, training, question answer, with the theme of "Essen und Trinken" (food and bevearage) in a form of demonstration. The teachers associated in MGMP of German respond well by involving actively   in every activity to promote their speaking skills. Most teacher felt satisfied and confessed that the activity is beneficial for them. They also get the new teaching method through Schlangenleiterspiel.